Let's Become A Humanist Communicator! The Importance of Interpersonal Communication Skills to Improve Group Cohesion - Artyanti Putri, Putu Riana; Winayanti, Ratna Devy; Artayasa, I Nyoman; Pramana, Ida Bagus Gde Yoga; Apsari, Ayu Rahmadita; Anggreni, Ni Wayan Yuli (Psikoborneo: Jurnal Ilmiah Psikologi, 2024)
The adolescent phase is a very critical development spear in life. Adolescents who have entered the age of high school students have experienced several significant changes that include emotional, cognitive, and social. School life not only revolves around understanding the material and working on tasks individually, but also includes good social interaction. In response to this, students are required to be able to blend in well to achieve social interaction with peers. It is important to have attachment between students to avoid prolonged conflicts between students and student groups. However, there are still many cases of conflict that occur due to low adhesion between students at school. The purpose of this study is to improve group cohesiveness by providing interpersonal communication training. The assumption of this interpersonal communication training is that by improving the interpersonal communication skills of participants, it will increase group cohesiveness in participants as well. This study is experimental research conducted on 14 students of class X IPS 1. There was a significant difference between the cohesiveness score of the group before and after the training with a sig value = 0.009 (p > 0.05), which showed that there was an increase in the cohesiveness score of the group of trainees. Based on the results of the research found, there was a change in behavior in class X IPS 1 student to become more blended and have more attachment to each other in class so that the classroom atmosphere became more synergistic and harmonious.Fase remaja menjadi tombak perkembangan yang sangat kritis di kehidupan. Remaja yang sudah memasuki usia peserta didik SMA telah mengalami sejumlah perubahan signifikan yang mencakup emosi, kognitif, dan sosial. Kehidupan sekolah tidak hanya berputar pada pemahaman materi dan pengerjaan tugas secara individu, tetapi juga mencakup interaksi sosial yang baik. Menanggapi hal tersebut, siswa diharuskan mampu untuk berbaur dengan baik guna mencapai interaksi sosial dengan teman sebaya. Penting memiliki kelekatan antar siswa untuk terhindar dari konflik berkepanjangan antar siswa maupun kelompok siswa. Akan tetapi, masih banyak sekali kasus konflik yang terjadi akibat rendahnya kelekatan antar siswa di sekolah. Tujuan dari penelitian ini adalah untuk meningkatkan kohesivitas kelompok dengan memberikan pelatihan komunikasi interpersonal. Asumsi dari pelatihan komunikasi interpersonal ini adalah dengan meningkatkan kemampuan komunikasi interpersonal peserta maka akan meningkatkan kohesivitas kelompok pada peserta pula. Penelitian ini merupakan penelitian eksperimen yang dilakukan terhadap 14 orang siswa kelas X IPS 1. Terdapat perbedaan yang yang signifikan antara skor kohesivitas kelompok sebelum pelatihan dan sesudah pelatihan dengan nilai sig = 0,009 (p > 0,05), hal ini menunjukkan bahwa terjadi peningkatan skor kohesivitas kelompok peserta pelatihan. Berdasarkan hasil penelitian yang ditemukan, terjadi perubahan perilaku pada siswa-siswa kelas X IPS 1 menjadi lebih berbaur dan lebih memiliki kelekatan antar satu sama lain di kelas sehingga suasana kelas menjadi lebih bersinergi dan rukun.